(untitled) (World Bulletin of Social Sciences, 2025)
Information is provided about the assistance provided by our people to the population relocated to our country from various regions due to World War II. The population of the cities and villages of the republic welcomed the citizens who came here with hospitality. The population gave them housing and lived in cramped conditions, even giving the last piece of bread to feed the immigrants, provided them with shoes, clothes, and hats, and spoke about the fortitude of Uzbek women